Ultra-high molecular weight polyethylene composite material and preparation method and application thereof
By using concave and convex rock stone nanofiber-clay mineral nanosheet mixture and mixed hybrid filler with surface-loaded silica in ultra-high molecular weight polyethylene, the wear problem of ultra-high molecular weight polyethylene under friction conditions is solved, and the wear problem of ultra-high molecular weight polyethylene is achieved. High wear resistance and low friction coefficient of composite materials.
Patent Information
- Application Number
- CN202410138092.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-01-31
AI Technical Summary
Ultra-high molecular weight polyethylene is susceptible to stress and deformation under friction conditions, resulting in a decrease in friction and wear performance, and the interface force between silica and the matrix is insufficient, resulting in the disengagement of the filler and increasing friction and wear.
The mixture of concave and convex stone nanofiber-clay mineral nanosheets is used as a mixed hybrid filler, and silica is loaded on its surface. Through mechanical mixing and hot pressing sintering, the degree of dispersion of the filler in the matrix and the interfacial bonding strength are improved. .
It significantly reduces the friction coefficient and wear rate of the composite material, improves hardness and wear resistance, enhances the interface combination between the filler and the matrix, and improves the friction reduction performance of the material.
Smart Images

Figure CN117964961B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wear-resistant materials, and in particular relates to an ultra-high molecular weight polyethylene composite material and a preparation method and application thereof. Background Art
[0002] Polymer-based composite materials have the advantages of low friction, low density, corrosion resistance, and easy modification. They gradually replace some metal parts and are used under mechanical friction conditions. Ultra-high molecular weight polyethylene (UHMWPE) is a thermoplastic engineering plastic with excellent corrosion resistance, high impact resistance and high wear resistance. It is widely used in the preparation of friction workpieces such as water-lubricated bearings, artificial joints, and bridge bearings. However, the surface hardness of ultra-high molecular weight polyethylene is low and its creep resistance is poor. It is easily deformed by stress during actual service, resulting in decreased friction and wear performance. Therefore, ultra-high molecular weight polyethylene can be filled and modified. Silica is an inorganic filler with small size and many micropores. After being added to the UHMWPE matrix, it can improve the strength and wear resistance of UHMWPE. However, since UHMWPE is a non-polar material, there is almost no chemical bond between it and the filler, so there is no interfacial force between silica and the resin matrix. Simple mechanical mixing cannot improve the interaction between the filler and the resin. The filler continues to fall out during the friction process, resulting in increased friction and wear of the composite material. At the same time, nano-silica agglomerates in the matrix, destroying the continuity of the matrix and having a great impact on the mechanical properties of the composite material. Therefore, how to improve the interface performance and mechanical properties between silica and the matrix while reducing the friction coefficient of the composite material is a technical problem that needs to be solved urgently. Summary of the invention
[0003] The purpose of the present invention is to provide an ultra-high molecular weight polyethylene composite material and a preparation method and application thereof. The ultra-high molecular weight polyethylene composite material provided by the present invention has excellent friction reduction and wear resistance.
[0004] In order to achieve the above object, the present invention provides the following technical solutions:
[0005] The present invention provides an ultra-high molecular weight polyethylene composite material, comprising the following components in parts by weight: 93.9-98.5 parts of ultra-high molecular weight polyethylene, 0.3-5 parts of mixed-dimensional hybrid filler and 0.8-1.1 parts of coupling agent;
[0006] The mixed-dimensional hybrid filler comprises a mixture of attapulgite nanofibers and clay mineral nanosheets and silicon dioxide loaded on the surface of the mixture of attapulgite nanofibers and clay mineral nanosheets.
[0007] Preferably, the molecular weight of the ultra-high molecular weight polyethylene is (6-9)×10 6g / mol;
[0008] The coupling agent is a silane coupling agent.
[0009] Preferably, the mass ratio of attapulgite nanofibers to clay mineral nanosheets in the attapulgite nanofiber-clay mineral nanosheet mixture is 1:1 to 1.5;
[0010] The mass ratio of the attapulgite nanofiber-clay mineral nanosheet mixture to silicon dioxide is 1:0.5-0.8.
[0011] Preferably, the method for preparing the mixed-dimensional hybrid filler comprises the following steps:
[0012] Mixing attapulgite nanofibers and clay mineral nanosheets to obtain a attapulgite nanofiber-clay mineral nanosheet mixture;
[0013] The attapulgite nanofiber-clay mineral nanosheet mixture, tetraethyl orthosilicate, ethanol and glacial acetic acid are mixed, and hydrolysis reaction and calcination are carried out in sequence to obtain the mixed-dimensional hybrid filler.
[0014] Preferably, the volume ratio of tetraethyl orthosilicate, ethanol and glacial acetic acid is 1:3-4:0.2-0.3;
[0015] The mass ratio of the attapulgite nanofiber-clay mineral nanosheet mixture to the total volume of ethyl orthosilicate, ethanol and glacial acetic acid is 1 g: 8 to 12 mL.
[0016] Preferably, the temperature of the hydrolysis reaction is 55-65° C. and the time is 2-4 hours.
[0017] Preferably, the calcination temperature is 450-550° C. and the calcination time is 120-180 min.
[0018] The present invention also provides a method for preparing the ultra-high molecular weight polyethylene composite material described in the above technical solution, comprising the following steps:
[0019] Mixing ultra-high molecular weight polyethylene, mixed-dimensional hybrid filler and coupling agent solution to obtain a mixed material;
[0020] The mixed material is hot-pressed and sintered to obtain the ultra-high molecular weight polyethylene composite material.
[0021] Preferably, the hot pressing sintering is performed at a pressure of 8 to 15 MPa, a temperature of 200 to 220° C., and a heat preservation time of 30 to 50 min.
[0022] The present invention also provides the use of the ultra-high molecular weight polyethylene composite material described in the above technical solution or the ultra-high molecular weight polyethylene composite material obtained by the preparation method described in the above technical solution in friction workpieces.
[0023] The present invention provides an ultra-high molecular weight polyethylene composite material, comprising the following components in mass fractions: 93.9-98.5 parts of ultra-high molecular weight polyethylene, 0.3-5 parts of mixed-dimensional hybrid filler and 0.8-1.1 parts of coupling agent; the mixed-dimensional hybrid filler comprises a mixture of attapulgite nanofiber-clay mineral nanosheets and silicon dioxide loaded on the surface of the mixture of attapulgite nanofiber-clay mineral nanosheets. In the ultra-high molecular weight polyethylene composite material provided by the present invention, attapulgite is a magnesium-rich aluminum silicate clay mineral with good heat resistance and large specific surface area. It can be added to an ultra-high molecular weight polyethylene matrix as a filler to reduce the friction coefficient of the composite material. By using one-dimensional attapulgite nanofibers and two-dimensional clay mineral nanosheets loaded with silicon dioxide on the surface as mixed-dimensional hybrid fillers, the dispersion degree of the filler in the matrix can be improved, the interface bonding strength with the matrix can be enhanced, the hardness of the composite material can be improved, and the friction coefficient and wear rate can be greatly reduced. The obtained ultra-high molecular weight polyethylene composite material has excellent friction reduction and wear resistance, and has excellent performance as a solid lubricant. It can be seen from the test results of the embodiments that the present invention improves the interface bonding and friction reduction effect of silica and ultra-high molecular weight polyethylene. The interface bonding between the filler and the matrix in the obtained ultra-high molecular weight polyethylene composite material is better than that of the silica ultra-high molecular weight polyethylene composite material, and while ensuring the excellent wear resistance of the material, the friction coefficient is also reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0025] Figure 1 The Shore hardness data diagram of ultra-high molecular weight polyethylene, ultra-high molecular weight polyethylene composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2;
[0026] Figure 2 The cross-sectional morphology scanning electron microscope images are of ultra-high molecular weight polyethylene, ultra-high molecular weight polyethylene composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2, wherein (a) to (f) correspond to ultra-high molecular weight polyethylene, ultra-high molecular weight polyethylene composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2, respectively;
[0027] Figure 3The friction coefficient data diagram of ultra-high molecular weight polyethylene, ultra-high molecular weight polyethylene composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2;
[0028] Figure 4 This is a data graph of specific wear rate of ultra-high molecular weight polyethylene, ultra-high molecular weight polyethylene composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2. DETAILED DESCRIPTION
[0029] The present invention provides an ultra-high molecular weight polyethylene composite material, comprising the following components in parts by weight: 93.9-98.5 parts of ultra-high molecular weight polyethylene, 0.3-5 parts of mixed-dimensional hybrid filler and 0.8-1.1 parts of coupling agent;
[0030] The mixed-dimensional hybrid filler comprises a mixture of attapulgite nanofibers and clay mineral nanosheets and silicon dioxide loaded on the surface of the mixture of attapulgite nanofibers and clay mineral nanosheets.
[0031] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.
[0032] The ultra-high molecular weight polyethylene composite material provided by the present invention comprises 93.9 to 98.5 parts of ultra-high molecular weight polyethylene, preferably 95 to 97 parts; the molecular weight of the ultra-high molecular weight polyethylene is (6 to 9)×10 6 g / mol, more preferably (6.5 to 8.5)×10 6 g / mol, and the most preferred value is (7.0-8.0)×10 6 g / mol.
[0033] Based on the mass fraction of the ultra-high molecular weight polyethylene, the ultra-high molecular weight polyethylene composite material provided by the present invention also includes 0.3 to 5 parts of mixed-dimensional hybrid filler, preferably 0.5 to 3 parts; the mixed-dimensional hybrid filler includes a attapulgite nanofiber-clay mineral nanosheet mixture and silicon dioxide loaded on the surface of the attapulgite nanofiber-clay mineral nanosheet mixture; the mass ratio of attapulgite nanofiber and clay mineral nanosheet in the attapulgite nanofiber-clay mineral nanosheet mixture is preferably 1:1 to 1.5, more preferably 1:1 to 1.3; the mass ratio of the attapulgite nanofiber-clay mineral nanosheet mixture to silicon dioxide is preferably 1:0.5 to 0.8, more preferably 1:0.5 to 0.6.
[0034] In the present invention, the preparation method of the mixed-dimensional hybrid filler comprises the following steps:
[0035] Mixing attapulgite nanofibers and clay mineral nanosheets to obtain a attapulgite nanofiber-clay mineral nanosheet mixture;
[0036] The attapulgite nanofiber-clay mineral nanosheet mixture, tetraethyl orthosilicate, ethanol and glacial acetic acid are mixed, and hydrolysis reaction and calcination are carried out in sequence to obtain the mixed-dimensional hybrid filler.
[0037] The present invention mixes attapulgite nanofibers and clay mineral nanosheets to obtain a attapulgite nanofiber-clay mineral nanosheet mixture.
[0038] In the present invention, the clay mineral nanosheets are preferably illite clay mineral nanosheets.
[0039] In the present invention, the mixing preferably further includes performing a first pretreatment and a second pretreatment on the attapulgite nanofibers and the clay mineral nanosheets, respectively.
[0040] In the present invention, the first pretreatment preferably includes: mixing attapulgite nanofibers and water, adjusting pH, aging, dispersing, drying and grinding in sequence; before the mixing, when the particle size of the attapulgite nanofibers is below 200 meshes, the present invention further preferably includes pre-grinding the attapulgite nanofibers; the present invention has no special limitation on the pre-grinding process, and the particle size of the attapulgite nanofibers can be made to reach 200 meshes or more in a manner well known to those skilled in the art; the water is preferably deionized water; the present invention has no special limitation on the mixing process, and a suspension can be obtained in a manner well known to those skilled in the art; the mass concentration of the attapulgite nanofibers in the suspension obtained by mixing is preferably 5-10%, more preferably 6-8 %; the pH value after adjusting the pH is preferably 9-11, more preferably 10-11; the aging temperature is preferably 20-30°C, more preferably 25-30°C; the time is preferably 28-36h, more preferably 24-36h; the dispersion method is preferably magnetic stirring; the speed of the magnetic stirring is preferably 200-280rpm, more preferably 240-280rpm; the time is preferably 3-5h, more preferably 4-5h; the drying temperature is preferably 50-70°C, more preferably 60-70°C; the time is preferably 10-15h, more preferably 12-15h; the present invention does not have any special limitation on the grinding process, and the particle size of the attapulgite nanofibers can be made to reach 400 mesh or more in a manner well known to those skilled in the art.
[0041] In the present invention, the second pretreatment preferably includes: mixing clay mineral nanosheets and hydrochloric acid dilution, and sequentially performing acidification reaction, filtering, washing and drying; the volume ratio of hydrochloric acid to water in the hydrochloric acid dilution is preferably 1:8-10, more preferably 1:9-10; the mass percentage of hydrogen chloride in the hydrochloric acid is preferably 30-40%, more preferably 37%; the mass concentration of clay mineral nanosheets in the suspension obtained by mixing is preferably 15-25%, more preferably 18-22%; the time of the acidification reaction is preferably 8-10h, more preferably 9-10h; the present invention does not have any special limitation on the filtering process, and a method well known to those skilled in the art can be used; the present invention does not have any special limitation on the filtering process, and washing to neutrality can be used in a method well known to those skilled in the art; the drying temperature is preferably 100-130°C, more preferably 120-130°C; the time is preferably 6-8h, more preferably 7-8h.
[0042] In the present invention, the mixing method is ball milling; the rotation speed of the ball mill is preferably 280 to 320 rpm, more preferably 30 to 320 rpm; the time is preferably 20 to 30 min, more preferably 25 to 30 min.
[0043] After obtaining the attapulgite nanofiber-clay mineral nanosheet mixture, the present invention mixes the attapulgite nanofiber-clay mineral nanosheet mixture, tetraethyl orthosilicate, ethanol and glacial acetic acid, and sequentially performs hydrolysis reaction and calcination to obtain the mixed-dimensional hybrid filler.
[0044] In the present invention, the volume ratio of tetraethyl orthosilicate, ethanol and glacial acetic acid is preferably 1:3-4:0.2-0.3, and more preferably 1:3.5-4:0.2-0.25; the mass of the attapulgite nanofiber-clay mineral nanosheet mixture and the total volume ratio of tetraethyl orthosilicate, ethanol and glacial acetic acid is preferably 1g:8-12mL, and more preferably 1g:10-12mL.
[0045] In the present invention, the mixing order is preferably to first mix tetraethyl orthosilicate, ethanol and glacial acetic acid, and then mix them with the attapulgite nanofiber-clay mineral nanosheet mixture; the first stirring time is preferably 20 to 30 minutes, more preferably 25 to 30 minutes; the present invention does not have any special limitation on the first stirring process, and a uniform and stable mixed solution can be obtained by a process well known to those skilled in the art; the second stirring is preferably magnetic stirring; the speed of the magnetic stirring is 150 to 200 rpm, more preferably 180 to 200 rpm; the time is 30 to 60 minutes, more preferably 40 to 60 minutes.
[0046] In the present invention, the mixing preferably also includes filtration and dispersion performed in sequence; the present invention does not have any special limitation on the filtration process, and a method familiar to those skilled in the art may be used; the dispersion solvent of the dispersion is preferably ethanol; the volume of the ethanol and the mass ratio of the solid obtained by filtration is preferably 3-5 mL:1 g, more preferably 4-5 mL:1 g; the dispersion method is preferably stirring; the stirring speed is preferably 60-120 rpm, more preferably 80-100 rpm; the time is preferably 30-60 min, more preferably 40-60 min.
[0047] In the present invention, the role of the suction filtration is to remove excess precursor solution in order to avoid self-agglomeration of the precursor solution after hydrolysis in the subsequent reaction process, thereby affecting the dispersibility of the composite filler.
[0048] In the present invention, the temperature of the hydrolysis reaction is preferably 55-65°C, more preferably 60-65°C; the time is preferably 2-4h, more preferably 3h; the hydrolysis reaction is preferably a steam hydrolysis reaction; the method of providing the hydrolysis reaction conditions is preferably to place a beaker containing the hydrolysis reaction liquid in a large beaker with an interlayer sealed; the large beaker preferably includes distilled water; the volume ratio of ethanol to distilled water is preferably 1:2-2.5, more preferably 1:2.2-2.5; the method of providing the hydrolysis reaction temperature is preferably water bath heating.
[0049] In the present invention, the hydrolysis reaction preferably further includes aging and drying in sequence; the aging time is preferably 12 to 16 hours, more preferably 12 to 14 hours; the drying temperature is preferably 60 to 80°C, more preferably 60 to 70°C; the drying time is preferably 6 to 8 hours, more preferably 6 to 7 hours.
[0050] In the present invention, the calcination temperature is preferably 450-550°C, more preferably 500-550°C; the heating rate is preferably 5-10°C / min, more preferably 6-8°C / min; the calcination time is preferably 120-180min, more preferably 120-150min.
[0051] Based on the mass fraction of the ultra-high molecular weight polyethylene, the ultra-high molecular weight polyethylene composite material provided by the present invention further includes 0.8 to 1.1 parts of a coupling agent, preferably 0.8 to 1 parts; the coupling agent is preferably a silane coupling agent; the silane coupling agent is preferably KH550 silane coupling agent or KH560 silane coupling agent.
[0052] In the ultra-high molecular weight polyethylene composite material provided by the present invention, attapulgite is a magnesium-rich aluminum silicate clay mineral with good heat resistance and large specific surface area. It can be added as a filler to the ultra-high molecular weight polyethylene matrix to reduce the friction coefficient of the composite material. By using one-dimensional attapulgite nanofibers with surface-loaded silica and two-dimensional clay mineral nanosheets to in-situ load silica microspheres as mixed-dimensional hybrid fillers, the filler and the matrix rely on van der Waals force to combine, which can improve the dispersion of the filler in the matrix, enhance the interface bonding strength with the matrix, improve the hardness of the composite material, and greatly reduce the friction coefficient and wear rate. The obtained ultra-high molecular weight polyethylene composite material has excellent friction reduction and wear resistance, and has excellent performance as a solid lubricant. It can be seen from the test results of the embodiment that the present invention improves the interface bonding and friction reduction effect of silica and ultra-high molecular weight polyethylene. The interface bonding between the filler and the matrix in the obtained ultra-high molecular weight polyethylene composite material is better than that of the silica ultra-high molecular weight polyethylene composite material, and while ensuring the excellent wear resistance of the material, the friction coefficient is also reduced.
[0053] The present invention also provides a method for preparing the ultra-high molecular weight polyethylene composite material described in the above technical solution, comprising the following steps:
[0054] Mixing ultra-high molecular weight polyethylene, mixed-dimensional hybrid filler and coupling agent solution to obtain a mixed material;
[0055] The mixed material is hot-pressed and sintered to obtain the ultra-high molecular weight polyethylene composite material.
[0056] The invention mixes ultra-high molecular weight polyethylene, mixed-dimensional hybrid filler and coupling agent solution to obtain a mixed material.
[0057] In the present invention, the coupling agent solution solvent is preferably ethanol; the mass ratio of the coupling agent to ethanol in the coupling agent solution is preferably 1:8-12, more preferably 1:10-12.
[0058] In the present invention, the mixing is preferably mechanically mixing the ultra-high molecular weight polyethylene and the mixed-dimensional hybrid filler, and spraying the coupling agent solution at the same time; the equipment for the mechanical mixing is preferably a mechanical dispersion sand mill, and more preferably an SDF400 experimental dispersion sand mill; the rotation speed of the mechanical mixing is preferably 1500-2500r / min, and more preferably 2000-2500r / min; the time is preferably 10-15min, and more preferably 10-13min.
[0059] In the present invention, the mixing preferably further includes drying; the drying temperature is preferably 60 to 70° C., more preferably 60 to 65° C.; the drying time is preferably 100 to 120 min, more preferably 110 to 120 min.
[0060] After obtaining the mixed material, the present invention performs hot pressing and sintering on the mixed material to obtain the ultra-high molecular weight polyethylene composite material.
[0061] In the present invention, the pressure of the hot pressing sintering is preferably 8-15MPa, more preferably 10-12MPa; the temperature is preferably 200-220°C, more preferably 205-215°C; the holding time is preferably 30-50min, more preferably 35-45min; the heating process of the hot pressing sintering preferably includes a first heating and a second heating performed in sequence; the final temperature of the first heating is preferably 180-200°C, more preferably 185-195°C; the heating rate is preferably 3-5°C / min, more preferably 3-4°C / min; the final temperature of the second heating is preferably 200-220°C, more preferably 205-215°C; the heating rate is preferably 1-2°C / min, more preferably 1°C / min.
[0062] In the present invention, the hot pressing sintering preferably further includes cooling and demolding in sequence; the cooling is preferably natural cooling; the demolding temperature is 70 to 80°C, more preferably 70 to 75°C.
[0063] The present invention also provides the use of the ultra-high molecular weight polyethylene composite material described in the above technical solution or the ultra-high molecular weight polyethylene composite material obtained by the preparation method described in the above technical solution in friction workpieces.
[0064] In the present invention, the friction workpiece is preferably a water-lubricated bearing friction workpiece, an artificial joint friction workpiece or a bridge bearing friction workpiece.
[0065] The present invention does not have any special limitation on the application of the ultra-high molecular weight polyethylene composite material in the friction workpiece, and any method familiar to those skilled in the art may be used.
[0066] In order to further illustrate the present invention, the ultra-high molecular weight polyethylene composite material provided by the present invention and its preparation method and application are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.
[0067] Example 1
[0068] The attapulgite was ground to less than 200 mesh, and prepared into a suspension with a mass concentration of 5% with distilled water. The pH value of the suspension was adjusted to 11, aged at 25° C. for 24 hours, dispersed with magnetic stirring for 4 hours (240 rpm), dried at 60° C. for 12 hours, and ground through a 400-mesh sieve to obtain purified attapulgite nanofibers.
[0069] Hydrochloric acid with a mass percentage of 37% is mixed with deionized water in a volume ratio of 1:10, and the two-dimensional illite clay mineral is added to the diluted hydrochloric acid solution to obtain a two-dimensional illite clay mineral suspension with a mass concentration of 20%. The suspension is stirred for acidification reaction, filtered and washed to neutral after 10 hours, and dried at 120°C for 8 hours to obtain the purified two-dimensional illite clay mineral.
[0070] The purified attapulgite nanofibers and two-dimensional illite clay minerals were mixed in a mass ratio of 1:1 by ball milling at 300 rpm for 30 minutes; tetraethyl orthosilicate, ethanol and glacial acetic acid were stirred in a volume ratio of 1:4:0.2 for 30 minutes; 4 g of the mixed mixed attapulgite was added to 40 mL of tetraethyl orthosilicate aqueous solution, and magnetic stirring was performed at 200 rpm for 60 minutes to obtain a uniformly dispersed suspension.
[0071] The suspension was filtered and then dispersed again. The mass ratio of ethanol to the filtered mixed-dimensional attapulgite-ethyl orthosilicate precursor was 5mL:1g. The suspension was placed in a beaker, and the outer large beaker was sealed with a funnel-shaped glass cover. The volume of distilled water in the large beaker was 2.5 times that of the mixed-dimensional attapulgite-ethyl orthosilicate precursor dispersion. The suspension was placed in a water bath with magnetic stirring and dispersed at a speed of 100rpm for 40min. The suspension was heated at a constant temperature of 60°C for steam hydrolysis. The reaction was completed after 3h. The product was aged for 12h, dried in an oven at 60°C for 6h, heated at a rate of 8°C / min, and calcined at 550°C for 120min to obtain a mixed-dimensional hybrid filler.
[0072] 30g of molecular weight is 7.8×10 6 g / mol of dry ultra-high molecular weight polyethylene and 0.6g of mixed-dimensional hybrid filler are placed in an SDF400 experimental dispersion sand mill, and mechanically mixed at a speed of 2000r / min for 10min. During the dispersion process, 3g of KH550 silane coupling agent dispersion is sprayed, and the mass ratio of the coupling agent to water in the silane coupling agent dispersion is 1:10 to obtain a mixed material; the mixed material is dried at 60°C for 120min and then cooled to room temperature, 3.5g of the above material is loaded into a stainless steel mold, and sintered in a 5-ton hot press with a sintering pressure of 10MPa. The sintering procedure is as follows: heating from room temperature to 200°C at a heating rate of 3°C / min, and then heating to 220°C at a heating rate of 1°C / min, keeping warm for 30min, naturally cooling to 70°C for demoulding, and obtaining a silica-mixed-dimensional attapulgite modified ultra-high molecular weight polyethylene composite material with a diameter of 25mm and a thickness of 8mm.
[0073] Example 2
[0074] Purified attapulgite nanofibers and two-dimensional illite clay minerals were prepared according to the technical solution provided in Example 1.
[0075] The purified attapulgite nanofibers and two-dimensional illite clay minerals were mixed by ball milling at a mass ratio of 1:1.5 at 300 rpm for 30 minutes; tetraethyl orthosilicate, ethanol and glacial acetic acid were stirred at a volume ratio of 1:4:0.2 for 20 minutes; 4 g of the mixed mixed attapulgite was added to 40 mL of tetraethyl orthosilicate aqueous solution, and magnetic stirring was performed at 200 rpm for 40 minutes to obtain a uniformly dispersed suspension.
[0076] The suspension was filtered and then dispersed again. The mass ratio of ethanol to the filtered mixed-dimensional attapulgite-ethyl orthosilicate precursor was 5mL:1g. The suspension was placed in a beaker, and the outer large beaker was sealed with a funnel-shaped glass cover. The volume of distilled water in the large beaker was 2.5 times that of the mixed-dimensional attapulgite-ethyl orthosilicate precursor dispersion. The suspension was placed in a water bath with magnetic stirring and dispersed at a speed of 80rpm for 40min. The suspension was heated at a constant temperature of 60°C for steam hydrolysis. The reaction was completed after 3h. The product was aged for 12h, dried in an oven at 60°C for 6h, heated at a rate of 8°C / min, and calcined at 500°C for 180min to obtain a mixed-dimensional hybrid filler.
[0077] 50g molecular weight is 7.8×10 6 g / mol of dry ultra-high molecular weight polyethylene and 0.5g of mixed-dimensional hybrid filler are placed in an SDF400 experimental dispersion sand mill, and mechanically mixed at a speed of 2000r / min for 10min. During the dispersion process, 5g of KH550 silane coupling agent dispersion is sprayed, and the mass ratio of the coupling agent to water in the silane coupling agent dispersion is 1:10 to obtain a mixed material; the mixed material is dried at 60°C for 120min and then cooled to room temperature, 3.5g of the above material is loaded into a stainless steel mold, and sintered in a 5-ton hot press with a sintering pressure of 10MPa. The sintering procedure is as follows: heating from room temperature to 180°C at a heating rate of 3°C / min, and then heating to 200°C at a heating rate of 1°C / min, keeping warm for 30min, naturally cooling to 70°C for demoulding, and obtaining a silica-mixed-dimensional attapulgite modified ultra-high molecular weight polyethylene composite material with a diameter of 25mm and a thickness of 8mm.
[0078] Example 3
[0079] Purified attapulgite nanofibers and two-dimensional illite clay minerals were prepared according to the technical solution provided in Example 1.
[0080] Purified attapulgite nanofibers and two-dimensional illite clay minerals were mixed by ball milling at a mass ratio of 1:1 at 320 rpm for 25 min; tetraethyl orthosilicate, ethanol and glacial acetic acid were stirred at a volume ratio of 1:4:0.3 for 30 min; 5 g of the mixed mixed attapulgite was added to 60 mL of tetraethyl orthosilicate aqueous solution, and magnetic stirring was performed at 150 rpm for 60 min to obtain a uniformly dispersed suspension.
[0081] The suspension was filtered and then dispersed again. The mass ratio of ethanol to the filtered mixed-dimensional attapulgite-ethyl orthosilicate precursor was 5mL:1g. The suspension was placed in a beaker, and the outer large beaker was sealed with a funnel-shaped glass cover. The volume of distilled water in the large beaker was 2.5 times that of the mixed-dimensional attapulgite-ethyl orthosilicate precursor dispersion. The suspension was placed in a water bath with magnetic stirring and dispersed at a speed of 100rpm for 40min. The suspension was heated at a constant temperature of 60°C for steam hydrolysis. After the reaction was complete after 3h, the product was aged for 16h, dried in an oven at 80°C for 6h, heated at a rate of 8°C / min, and calcined at 500°C for 120min to obtain a mixed-dimensional hybrid filler.
[0082] 30g of molecular weight is 7.8×10 6 g / mol of dry ultra-high molecular weight polyethylene and 0.15g of mixed-dimensional hybrid filler are placed in an SDF400 experimental dispersion sand mill, and mechanically mixed at a speed of 2000r / min for 10min. During the dispersion process, 3g of KH560 silane coupling agent dispersion is sprayed, and the mass ratio of the coupling agent to water in the silane coupling agent dispersion is 1:10 to obtain a mixed material; the mixed material is dried at 60°C for 120min and then cooled to room temperature, 3.5g of the above material is loaded into a stainless steel mold, and sintered in a 5-ton hot press with a sintering pressure of 10MPa. The sintering procedure is as follows: heating from room temperature to 190°C at a heating rate of 2°C / min, and then heating to 210°C at a heating rate of 1°C / min, keeping warm for 40min, naturally cooling to 70°C for demoulding, and obtaining a silica-mixed-dimensional attapulgite modified ultra-high molecular weight polyethylene composite material with a diameter of 25mm and a thickness of 8mm.
[0083] Comparative Example 1
[0084] Purified attapulgite nanofibers and two-dimensional illite clay minerals were prepared according to the technical solution provided in Example 1.
[0085] The purified attapulgite nanofibers and two-dimensional illite clay minerals were mixed in a mass ratio of 1:1 by ball milling at 320 rpm for 25 min.
[0086] 30g of molecular weight is 7.8×10 6g / mol of dry ultra-high molecular weight polyethylene and 0.15g of mixed-dimensional attapulgite are placed in an SDF400 experimental dispersion sand mill, and mechanically mixed at a speed of 2000r / min for 10min. During the dispersion process, 3g of KH560 silane coupling agent dispersion is sprayed to obtain a mixture; the mixture is dried at 60°C for 120min and then cooled to room temperature, 3.5g of the above materials are loaded into a stainless steel mold, and sintered in a 5-ton hot press with a sintering pressure of 10MPa. The sintering procedure is as follows: the temperature is increased from room temperature to 190°C at a heating rate of 2°C / min, and then the temperature is increased to 210°C at a heating rate of 1°C / min, and then the temperature is kept for 40min, and the mixture is naturally cooled to 70°C for demolding to obtain a mixed-dimensional attapulgite-modified ultra-high molecular weight polyethylene composite material with a diameter of 25mm and a thickness of 8mm.
[0087] Comparative Example 2
[0088] The tetraethyl orthosilicate, ethanol and glacial acetic acid were stirred at a volume ratio of 1:4:0.3 for 30 minutes; the tetraethyl orthosilicate precursor dispersion was placed in a beaker, the outer large beaker was sealed with a funnel-shaped glass cover, and placed in a water bath for magnetic stirring at a speed of 80 rpm and constant temperature heating at 60°C for steam hydrolysis. After the reaction, the obtained product was aged for 12 hours, dried in an oven at 60°C for 6 hours, heated at a rate of 8°C / min, and calcined at 500°C for 180 minutes to obtain nano silicon dioxide.
[0089] 30g of molecular weight is 7.8×10 6 g / mol of dry ultra-high molecular weight polyethylene and 0.15g of nano-silicon dioxide are placed in an SDF400 experimental dispersion sand mill, and mechanically mixed at a speed of 2000r / min for 10min. During the dispersion process, 3g of KH560 silane coupling agent dispersion is sprayed to obtain a mixed material; the mixed material is dried at 60°C for 120min and then cooled to room temperature, 3.5g of the above materials are loaded into a stainless steel mold, and sintered in a 5-ton hot press with a sintering pressure of 10MPa. The sintering procedure is as follows: heating from room temperature to 190°C at a heating rate of 2°C / min, and then heating to 210°C at a heating rate of 1°C / min, keeping the temperature for 40min, naturally cooling to 70°C for demoulding, and obtaining a silica-modified ultra-high molecular weight polyethylene composite material with a diameter of 25mm and a thickness of 8mm.
[0090] Test Example 1
[0091] The hardness of the ultra-high molecular weight polyethylene, the ultra-high molecular weight polyethylene composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was tested. The Shore hardness data are as follows: Figure 1 shown.
[0092] from Figure 1 It can be seen that after adding the silica-mixed attapulgite hybrid material, the hardness of the composite material is improved. The Shore hardness of pure ultra-high molecular weight polyethylene is about 58. The addition content of silica-mixed attapulgite hybrid material in Examples 1 to 3 is reduced successively. It is found that the increase in the content of hybrid fillers is conducive to the improvement of the hardness of the composite material. The material hardness increases, and the bearing capacity during the friction process is enhanced accordingly. The filler content of the composite material of Comparative Examples 1 to 2 is the same as that of Example 3. It is found that the improvement of the hardness of the composite material by single mixed attapulgite and nano-silica is limited. Among them, the addition of nano-silica with the same mass fraction has the least effect on the improvement of ultra-high molecular weight polyethylene.
[0093] Test Example 2
[0094] The microstructures of the ultra-high molecular weight polyethylene, the ultra-high molecular weight polyethylene composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were characterized. The cross-sectional morphology scanning electron microscope images are shown in FIG. Figure 2 shown.
[0095] from Figure 2 It can be seen that the surface of ultra-high molecular weight polyethylene is relatively flat. After adding silica-mixed attapulgite hybrid filler, there are obvious resin whiskers between the filler and the matrix, indicating that there is a strong van der Waals force between silica-mixed attapulgite and the matrix. This is due to the fact that the rough surface of the hybrid filler enhances the mechanical intercalation between the filler and the resin. Therefore, during the melting process, the ultra-high molecular weight polyethylene and the filler form a good infiltration, which ultimately improves the interface bonding strength between the filler and the resin. Figure 2 e. The mechanical intercalation between the mixed-dimensional attapulgite and the ultra-high molecular weight polyethylene matrix is significantly reduced, and the nano-silica agglomerates in the ultra-high molecular weight polyethylene matrix in Comparative Example 2. In summary, the silica-mixed-dimensional attapulgite hybrid filler has a better interface bonding with the ultra-high molecular weight polyethylene matrix.
[0096] Test Example 3
[0097] The friction properties of the ultra-high molecular weight polyethylene, polyetherimide-attapulgite-carbon fiber filled ultra-high molecular weight polyethylene composites prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested. The friction coefficient and specific wear rate were as follows: Figures 3-4 shown.
[0098] from Figures 3-4 It can be seen that the friction coefficient of pure ultra-high molecular weight polyethylene is about 0.41. After adding the silica-mixed-dimensional attapulgite hybrid material, the friction coefficient of the composite material is reduced, among which the friction coefficient of the composite material of Example 2 is reduced to 0.27, which is 34% lower than that of pure ultra-high molecular weight polyethylene.
[0099] The addition of silica-mixed attapulgite significantly reduces the friction coefficient of the composite material. This is because the one-dimensional attapulgite nanofibers and the two-dimensional illite nanosheets slip during the friction process, reducing the friction resistance of the composite material. Observing the specific wear rate of ultra-high molecular weight polyethylene and the composite material, the wear rates of Examples 1 to 3 and Comparative Example 1 are reduced to varying degrees. Example 2 has the best anti-wear performance, and the specific wear rate is 20% lower than that of pure ultra-high molecular weight polyethylene. The difference in friction coefficient and wear rate between Examples 1 to 3 and Comparative Examples 1 to 2 shows that compared with mixed dimensional attapulgite and nano-silica, silica-mixed attapulgite hybrid fillers can effectively reduce the friction and wear of composite materials.
[0100] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. An ultra-high molecular weight polyethylene composite material, characterized in that: The invention comprises the following components in parts by weight: 93.9 to 98.5 parts of ultra-high molecular weight polyethylene, 0.3 to 5 parts of mixed-dimensional hybrid filler and 0.8 to 1.1 parts of coupling agent; The mixed-dimensional hybrid filler comprises a mixture of attapulgite nanofibers and clay mineral nanosheets and silicon dioxide loaded on the surface of the mixture of attapulgite nanofibers and clay mineral nanosheets; the mass ratio of the mixture of attapulgite nanofibers and clay mineral nanosheets to silicon dioxide is 1:0.5-0.8; The preparation method of the mixed-dimensional hybrid filler comprises the following steps: Mixing attapulgite nanofibers and clay mineral nanosheets to obtain a attapulgite nanofiber-clay mineral nanosheet mixture; The attapulgite nanofiber-clay mineral nanosheet mixture, tetraethyl orthosilicate, ethanol and glacial acetic acid are mixed, and hydrolysis reaction and calcination are carried out in sequence to obtain the mixed-dimensional hybrid filler.
2. The ultra-high molecular weight polyethylene composite material according to claim 1, characterized in that: The molecular weight of the ultra-high molecular weight polyethylene is (6-9)×10 6 g / mol; The coupling agent is a silane coupling agent.
3. The ultra-high molecular weight polyethylene composite material according to claim 1, characterized in that: The mass ratio of the attapulgite nanofiber to the clay mineral nanosheet in the attapulgite nanofiber-clay mineral nanosheet mixture is 1:1-1.
5.
4. The ultra-high molecular weight polyethylene composite material according to claim 1, characterized in that: The volume ratio of the tetraethyl orthosilicate, ethanol and glacial acetic acid is 1:3-4:0.2-0.3; The mass ratio of the attapulgite nanofiber-clay mineral nanosheet mixture to the total volume of ethyl orthosilicate, ethanol and glacial acetic acid is 1 g: 8 to 12 mL.
5. The ultra-high molecular weight polyethylene composite material according to claim 1, characterized in that: The temperature of the hydrolysis reaction is 55-65° C. and the time is 2-4 hours.
6. The ultra-high molecular weight polyethylene composite material according to claim 1, characterized in that: The calcination temperature is 450-550° C. and the calcination time is 120-180 min.
7. The method for preparing the ultra-high molecular weight polyethylene composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Mixing ultra-high molecular weight polyethylene, mixed-dimensional hybrid filler and coupling agent solution to obtain a mixed material; The mixed material is hot-pressed and sintered to obtain the ultra-high molecular weight polyethylene composite material.
8. The preparation method according to claim 7, characterized in that: The hot pressing sintering is performed at a pressure of 8 to 15 MPa, a temperature of 200 to 220° C., and a heat preservation time of 30 to 50 minutes.
9. Use of the ultra-high molecular weight polyethylene composite material according to any one of claims 1 to 6 or the ultra-high molecular weight polyethylene composite material obtained by the preparation method according to claim 7 or 8 in friction workpieces.
Citation Information
Patent Citations
Preparation method of carbon fiber and silicon dioxide nanosphere synergically filled ultra-high molecular weight polyethylene wear-resistant material
CN107663328A
Wear-resistant material, preparation method thereof and wear-resistant product
CN111073117A